Association between Urinary Tract Infection, Gender, Age and the Occurrence of Magnesium Ammonium Phosphate compared with Calcium Oxalate Uroliths in Dogs - Detkalaya, Osathee; Vichukit, Karin; Kornkasem, Sajee; Thanaperm, Piyawan; Lekcharoensuk, Chalermpol (Journal of Mahanakorn Veterinary Medicine, 2020)
The objectives of this study were evaluated the associations between urinary tract infection, gender, age and magnesium ammonium phosphate urolith occurrences compared with calcium oxalate urolith occurrences in dogs visited at Kasetsart University Veterinary Teaching Hospital during 2016-2018. Urolith compositions were analyzed at Kasetsart University Urolith Center by infrared spectroscopy. Descriptive statistic and logistic regression were performed by the commercial software. The results of 701 urolith samples were analyzed. The common uroliths (638 submitted samples; 91.01%) were calcium oxalate (CaOx) and magnesium ammonium phosphate (struvite; MAP). The average age and standard deviation for dogs with CaOx uroliths was 9.1 ± 3.2 years, 7.0 ± 3.1 years for MAP, 6.8 ± 3.8 years for Purine, 3.4 ± 1.9 years for cystine, 7.6 ± 3.6 years for calcium phosphate (CaP), 5.0 ± 0.0 years for silica, 11.9 ± 2.9 years for compound and 5.7 ± 2.7 years for mixed uroliths. The top 3 bacterial urinary tract infections were 146 (54.89%) Staphylococcus spp., 32 (12.03%) E.coli, and 20 (7.52%) Proteus spp. Comparison with dogs with CaOx uroliths, the dogs with strong urease bacterial urinary tract infection has increased risk (OR=12.6, 95% CI=7.18-22.09) for developing MAP uroliths compared with dogs with no growth urine sample. The dogs less than 2 years old had increased risk (OR=21.9, 95%CI=2.7-179.06) for developing MAP uroliths compared with over 10 years old dogs. Female dogs had increased risk (OR=9.77, 95%CI=6.06-15.75) for developing MAP uroliths compared with male dogs. The result of multiple logistic regression indicated that dogs with strong urease bacterial urinary tract infection, female dogs and dogs less than 2 years old had increased risk for developing MAP uroliths compared with dogs with CaOx uroliths.